Students’ Perception towards the Use of Social Networking as an e-learning Platform - HARUN, JAMALLUDIN (2011)
The purpose of this study was to investigate students’ perceptions on the current elearning system and adopting social networking as a main platform of the university elearning. This study also explored the required skill for effective use of social networking tools. The population of this study were 600 final year students at one of the Faculties in a Malaysian’s university. Questionnaire was used as a research instrument to collect data from 234 respondents which had been selected randomly. Data had been analyzed using quantitative data analysis method, which were mean, percentage, and Independentsample T test. The findings of this study indicated that students satisfaction of current elearning system was in a moderately positive level (mean = 3.77). Students agreed on adopting social networking as an elearning platform (mean = 4.11) and they also agreed with all of the required skills for effectively use of social networking tools (mean = 4.17). From this study also, type of students’ study programme has no effect on students’ perception neither towards current e learning system nor in the required skills of using social networking effectively. However; there was a significant difference between male and female students in the required skills of using social networking tools at α = 0.05 ( p = 0.014). Female students appeared to be more skilful and ready for using social networking tools (mean = 4.23) than male students (mean = 4.07). From this research finding, it can be concluded that students preferred social networking as an elearning platform, where it can provide them more interactive features than the current elearning system.